New meaning for the emotional state of the elderly, from a leisure standpoint - Schwartz, Gisele Maria [UNESP]; Campagna, Jossett [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2008)
Continuing developments in science and technology that affect many dimensions of human life, especially those related to longevity, require responses from social policies and programmes to enable quality-of-life improvements in every sector, including leisure. To contribute to research in this area, this qualitative study sought to identify the perceptions of and meanings attached to participation in (active outdoor) leisure by a group of elderly citizens of Araras, São Paulo State, Brazil. Data were collected via questionnaires administered to a mixed-gender sample of 100 persons, aged between 60 and 80 years, after they had participated in an outdoor adventure/leisure programme. The data were subjected to thematic content analysis. The study revealed that the participants identified positive emotional effects as a result of their participation, relating to their sense of belonging to a group, to their increased quality of life and to their ability to remain physically active.
Keywords: leisure; emotion; elderly; adventure; activities; lifestyle